Depressive Symptoms in Heart Failure: Pathophysiology and Diagnosis - Taskura, Risfandi Ahmad; Murti Putri Utami (Scientia Psychiatrica, 2024)
Depression commonly affects individuals with heart failure and is associated with higher mortality rates, increased disability, healthcare costs, and reduced quality of life. Heart failure patients are more likely to experience depression. This study was aimed to describe pathophysiology and treatment of depression in heart failure patients. Both physiological and behavioral variables may influence the relationship between depression and the development and progression of heart failure, as well as increased rates of mortality. Because of the similarities between the symptoms of cardiac and mental illnesses, it may be difficult to make an appropriate diagnosis of depressive disorders in individuals who are suffering from heart failure. Further research is urgently needed to improve the diagnosis of these disorders and develop therapies that benefit patients with heart failure.